Proposta de intervenção psicológica para melhorar as estratégias de enfrentamento da criança hospitalizada - Vicente, Schwanny Roberta Costa Rambalducci Mofat (2017)
Hospitalization is considered a potential stressor for the child and his/her Family. For stress regulation, children use different coping strategies to deal with situations that they interpret as a threat or challenge to the physical and emotional dimensions. This research proposes to verify the effects of a brief, structured and ludic psychological intervention to improve the hospitalization coping strategies. The sample consisted of 60 children, aged between 7 and 12 years old, hospitalized between July and November of 2016 in a public hospital in the state, in addition to their caretakers. Participants were approached after 24 hours of hospitalization, a period necessary to experience stressors of hospitalization. Adopting an experimental design, with pre-test and post-test, the sample was randomly distributed into two groups with 30 children each: Group 1 (G1), which participated in the hospital activities; and Group 2 (G2), submitted to the hospitalization coping intervention. The caregivers answered, in the first evaluation stage, to the Identification Protocol, with general data about the child and about the hospitalization, and to the Parents’ Questionnaire as Social Context - PASC (parents’ report). The G1 and G2 children answered the Infant Stress Scale (ESI), the Hospitalization Coping Strategies Assessment (COPE-H) and the PASC (children’s report). Then, the G2 was submitted to the intervention centered on an instrument elaborated for this research, called Coping Clock, based on the Motivational Theory of Coping - MTC. After a period of 48 hours, with the hospital recreational routine for G1 and with the intervention for G2, the children answered to the same instruments of the first evaluation stage, with the addition of a questionnaire about the intervention acceptability for G2. Data was analyzed using descriptive and inferential statistics. The results indicated intervention quality and adequacy criteria to improve the adaptive resources of the child when dealing with hospitalization stressors, besides providing indicators on the feasibility of its application in other hospitalization contexts. In the PASC (parent’s report) of both groups, the dimension with highest mean was structure, followed by autonomy support. For the PASC (children's report), in both groups, the affect dimension obtained the highest mean. Regarding stress, the results indicated a significant reduction of the levels between pre and post-test in the intervention group. In the control group, there was a reduction of the stress symptoms total score mean in the post-test; however, it was not statistically significant. The COPE-H analysis showed a significant increase of voluntary and involuntary disengagement between pre and post-test in the control group; for the intervention group, there was an increase in adaptive coping and in voluntary and involuntary disengagement between pre and post-test. In the coping families’ analysis, there was a significant increase in the mean of the adaptive family between pre-test and post-test in the control group; for the intervention group, there was an increase in the mean of adaptive behaviors and a decrease in the mean of maladaptive behaviors. The proposed intervention demonstrated efficacy evidences, being important its application to a better children’s hospitalization adaptation.